The law of diminishing marginal utility as law of mental order-ness - Posvanc, Matus (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Nozick (1977) formulated a challenge to Austrians related to the application of the Law of diminishing marginal utility in the context of notion of indifference. To be able to claim that the value or attributed utility of the subsequent units of goods decreases, we must compare comparables, even if deliberate choice means that we have chosen a particular as being value-different. This causes a logical paradox. One cannot be indifferent and demonstrate a particular preference at the same time. It is mutually exclusive. The paper discusses a critique of Wysocki (2021), who proposes a solution to the paradox in terms of a counterfactual perception of the Law. The critique points to the essence of why neo-Misesians cannot resolve the paradox, which lies in the interpretation of the origin of valuation within the particular value scale. The paper offers an alternative solution based on Hayek’s concept of mental order-ness with the implication of the general applicability of the Law to any order in reality.